Ancaman Infodemi Sebagai Hambatan Penanganan Pandemi Covid-19 di Indonesia - Anastasyia Sukma Kundhalini; Mochammmad Afifuddin; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The large wave of information that occurred during the Covid-19 pandemic was caused by limited knowledge regarding this spreading disease. Information that is abundant and confusing and spreads quickly by WHO is called an infodemic. The infodemic resulted in the handling of the Covid-19 pandemic not being resolved easily because it changed people's perceptions and people's compliance with government policies. This study aims to discuss the infodemic that occurred in Indonesia during the 2020-2021 Covid-19 pandemic using a case study approach. This research found that during the Covid-19 pandemic in 2020-2021, the infodemic in Indonesia occurred in the form of hoaxes that affected the wider community so there was confusion of information that affected the handling of the pandemic.